Daily feeding frequency affects feed intake and body weight management of growing layers - Junjie Wang; Zengmin Liu; Hai Lin; Hongchao Jiao; Jingpeng Zhao; Baishun Ma; Yao Wang; Shuying He; Xiaojuan Wang (Poultry Science, 2024)
ABSTRACT: The objective of this study was to investigate the effect of feeding behavior on feed intake and body weight in growing layers and the underlying mechanisms, thereby providing a scientific foundation for optimal feeding practices in growing layers' management. A total of 144 Hy-line brown growing layers of 10 wk old and similar body weight, were divided into 3 treatment groups with different feeding frequency and equal cumulative daily feeding amount: the once-a-day feeding group (F1) was fed at 9:00 am every day, with feeding amount of 150 g/layer; the twice-a-day feeding group (F2) were fed at 9:00 am and 13:00 pm every day, with each feeding amount of 75 g/layer; the 4 times-a-day feeding group (F4) were fed at 9:00 am, 11:00 am, 13:00 pm, and 15:00 pm every day, with each feeding amount of 37.5 g/layer. Pre-experiment lasted for 1 wk and formal experiment lasted for 8 wk. The results indicated that the daily feed intake and body weight were decreased (P < 0.05) while feed conversion ratio was not affected (P > 0.05) as daily feeding times increased. The glandular stomach proportion was significantly increased in twice-a-day feeding group, while liver proportion and ileum length were significantly increased in 4 times-feeding group (P < 0.05). Additionally, 4 times-feeding daily resulted in a significant elevation of blood glucose levels, which may have suppressed feed intake (P < 0.05). In 4 times-feeding group, the plasma triglyceride levels increased as feeding times, accompanied by a notable up-regulation in the mRNA level of appetite-suppressing gene, hypothalamic pro-opiomelanocortin (POMC) and glandular stomach ghrelin. This modulation effectively suppressed the subsequent feed intake and body weight. Therefore, 4 times feeding daily is recommended in growing layers’ management, because it reduced the feed cost without affecting the feed conversion efficiency.